In-Situ Recovery of Butanol from Abe Fermentation Solution by Hydrophobic Ionic Liquid Perstraction in Tubular Membranes Assisted with Vacuum - Zuniga-Navarro, G; Romero-Figueroa, J; Quijada-Maldonado, E; Becerra-Navarrete, J (Elsevier B.V., 2023)
The selective removal of butanol from a fermentation broth continues to be a challenge for the generation of alternative biofuels. In this work, a continuous extraction of a model acetone-butanol-ethanol (ABE) solution, using a perstraction membrane system with ionic liquid [omim][Tf2N] as extractant phase coupled to a vacuum extraction system of the extractant phase has been studied. Perstraction assays were carried out using a tubular polydimethylsiloxane (PDMS) membrane to quantify the extraction percentage and transmembrane fluxes of butanol, acetone, ethanol, and water. The results indicate that the transmembrane fluxes of butanol were particularly high considering that the PDMS membrane used in the experiments was relatively thick (3.175 mm). The highest average flux of butanol was obtained at 37 °C using [omim][Tf2N] as extractant reaching a value of 1.17∙10-3 [kg h−1 m−2] with a separation performance showing a highest butanol/water selectivity value equal to 6.73. The mass transfer model based on the resistance-in-series theory, demonstrated a good correlation to the experimental data verifying that the membrane generates a higher resistance to mass transfer (∼98 %). This perstraction technique combined with the use of ILs could allow to design a wide range of separation processes to purify a large variety of molecules. Additionally, the perstraction process could be considered a good alternative for the selective separation of fermentation or reaction products with high commercial value. © 2023 Elsevier B.V.